Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species - Zhang, E.; Chen, Y.-Y. (Zootaxa, 2006)
Most morphological characters diagnostic of the 13 Chinese species of the cyprinid genus Sinilabeo Rendahl, 1932, are identical to those of the genus Bangana Hamilton, 1822. Consequently, these 13 species are transferred to Bangana. A revised diagnosis is provided for the now-expanded genus Bangana, and a dichotomous key and taxonomic and nomenclatural notes are included for the following valid Chinese species: B. decora, B. dero, B. devdevi, B. discognathoides, B. lemassoni, B. lippa, B. rendahli, B. tonkinensis, B. tungting, B. wui, B. xanthogenys, B. yunnanensis, and B. zhui. Literature reports, by Chinese authors, of Sinilabeo dero from the upper Irrawady River basin, in Yunnan, are based on misidentifcations of B. devdevi. Sinilabeo cirrhinoides Wu and Lin in Wu, Lin, Chen, Chen and He, 1977, and S. laticeps Wu and Lin in Wu, Lin, Chen, Chen and He, 1977, are junior subjective synonyms of B. devdevi and B. lippa, respectively. Sinilabeo yunnanensis Wu, Lin, Chen, Chen and He, 1977, is an available name, and a lectotype is designated for the species. Bangana zhui (Zheng and Chen, 1983) is a valid species distinct from B. yunnanensis.